2013
DOI: 10.5688/ajpe777146
|View full text |Cite
|
Sign up to set email alerts
|

Graduating Pharmacy Students’ Perspectives on E-Professionalism and Social Media

Abstract: Objective. To determine the use patterns of social media among graduating pharmacy students, characterize students' views and opinions of professionalism on popular social media sites, and compare responses about social media behavior among students seeking different types of employment. Methods. All graduating pharmacy students (n5516) at Purdue University, The University of Findlay, Butler University, and Midwestern University were invited to complete a survey instrument during the fall semester of 2011. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 12 publications
0
26
0
3
Order By: Relevance
“…6,11 The pilot test for the survey questions was conducted with 12 pharmacy students, and minor revisions were made based on the results from the pilot test. The survey instrument consisted of 20 questions regarding demographic data, SNS activities, and perceptions of e-professionalism.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…6,11 The pilot test for the survey questions was conducted with 12 pharmacy students, and minor revisions were made based on the results from the pilot test. The survey instrument consisted of 20 questions regarding demographic data, SNS activities, and perceptions of e-professionalism.…”
Section: Methodsmentioning
confidence: 99%
“…3,11 Approximately 45% of pharmacy students at Queen's University Belfast in the United Kingdom indicated that they had posted content that they did not want a prospective employer or university administrator to view. 11,12 A study analyzing the first-year pharmacy students in the United States reported that approximately 65% of these students indicated their online images on Facebook accurately showed future images as healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations